TRANMISSION AND PRESERVATION OF KHANOM BODIN AS INTANGIBLE CULTURAL HERITAGE OF THE SUAN PHLU MOSQUE COMMUNITY - Kaewya, Anupol; Peeraphatchara, Chutamas (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
This qualitative study employed a phenomenological approach to investigate the communal context of the Suan Phlu Mosque and analyzed the transmission and preservation of Khanom Bodin (a traditional Thai-Muslim dessert) as intangible cultural heritage. Data were elicited from selected ten purposive key informants—comprising community leaders, local experts, and artisanal practitioners—through semi-structured in-depth interviews, followed by thematic analysis and data triangulation. The findings revealed that the Suan Phlu Mosque community, historically defined by its betel nut plantations, maintained a distinct socio - cultural identity through its traditional Muslim gastronomy, particularly Khanom Bodin, which was intrinsically linked to Ramadan and matrimonial ceremonies. Regarding its continuity, while the culinary wisdom was traditionally inherited within families, the practice had contracted to a few households that adapted ingredients and techniques to contemporary demands. Despite its economic significance as a seasonal enterprise during religious festivals, the remaining of Khanom Bodin faced challenges from shifting consumption patterns among the younger generation. Consequently, the study emphasized the profoundly socio-religious value of this heritage followed by underscored the necessity of fostering public awareness and systematic knowledgeable transferability to ensure its long-term cultural sustainability.